Organoleptic Characteristics of Tongkat langit Banana Smoothie with Variations in Gum Arabic Concentration - Tetelepta, Gilian; Picauly, Priscillia (Pattimura University Ambon Maluku Indonesia, 2025)
This study aimed to determine the optimal concentration of gum arabic to produce the best banana tongkat langit smoothie, based on its organoleptic properties. The research design employed was a 1-factor Completely Randomized Design with Arabic gum concentration treatment, consisting of four levels: without gum arabic, 0.05%, 0.10%, and 0.15%, repeated three times. The variables analyzed included organoleptic tests, such as color, aroma, taste, texture, aftertaste, and overall impression. Based on the results of the study, it can be concluded that the 0.15% arabic gum concentration yielded the highets scores in color (3.12), aroma (2.82), taste (3.18), texture (3,24), aftertaste (2,94), and overall (12) liking, while based on hedonic quality it produces a yellow color (3,12), soft taste (3.12), and creamy texture (3.18).